2016
DOI: 10.3389/fmicb.2016.01342
|View full text |Cite
|
Sign up to set email alerts
|

Leisingera sp. JC1, a Bacterial Isolate from Hawaiian Bobtail Squid Eggs, Produces Indigoidine and Differentially Inhibits Vibrios

Abstract: Female members of many cephalopod species house a bacterial consortium in the accessory nidamental gland (ANG), part of the reproductive system. These bacteria are deposited into eggs that are then laid in the environment where they must develop unprotected from predation, pathogens, and fouling. In this study, we characterized the genome and secondary metabolite production of Leisingera sp. JC1, a member of the roseobacter clade (Rhodobacteraceae) of Alphaproteobacteria isolated from the jelly coat of eggs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 65 publications
(113 reference statements)
1
80
0
Order By: Relevance
“…JC1, a member of the roseobacter clade ( Rhodobacteraceae ) of Alphaproteobacteria. 25 As is characteristic of many cephalopod species, female Hawaiian bobtail squids house a bacterial community in the accessory nidamental gland (ANG), part of their reproductive systems. Bacteria are deposited into eggs that are then laid in locations where they are vulnerable to an assortment of threats as they must develop further.…”
Section: Animal-microbe Symbiosesmentioning
confidence: 99%
See 2 more Smart Citations
“…JC1, a member of the roseobacter clade ( Rhodobacteraceae ) of Alphaproteobacteria. 25 As is characteristic of many cephalopod species, female Hawaiian bobtail squids house a bacterial community in the accessory nidamental gland (ANG), part of their reproductive systems. Bacteria are deposited into eggs that are then laid in locations where they are vulnerable to an assortment of threats as they must develop further.…”
Section: Animal-microbe Symbiosesmentioning
confidence: 99%
“…JC1 is a critical element of the symbiont community in bobtail squid ANGs and that this bacterium houses a number of biosynthetic gene clusters (BGCs) for a number of secondary metabolites, including siderophores and quorum-associated acyl-homoserine lactones. 25 Leisingera sp. JC1 was found to produce the pigment indigoidine both, in isolation, and in co-culture conditions with Vibrio fischeri , the light organ bacterial symbiont of E. scolopes , as well as with other Vibrio spp.…”
Section: Animal-microbe Symbiosesmentioning
confidence: 99%
See 1 more Smart Citation
“…This gland is composed of many epithelium-lined tubules, containing a bacterial consortium dominated by members of the Alphaproteobacteria and Verrucomicrobia (Collins et al, 2012b). The bacteria are deposited into the egg jelly coats of squid where they are hypothesized to play a protective role during development (Collins et al, 2012b, 2015; Gromek et al, 2016). Like the light organ, the ANG is highly vascularized and hemocytes have been observed within the lumen of the tubules and in direct contact with bacteria ( Figure 1C ; Collins et al, 2012b).…”
Section: E Scolopes As a Model For Binary And Consortial Symbiosesmentioning
confidence: 99%
“…Studies in a number of animal-microbe symbioses have revealed that bacteria are active in a wide range of biological processes (McFall-Ngai et al, 2013), including digestion, host defense, development, and even camouflage (Gil-Turnes et al, 1989; McFall-Ngai and Montgomery, 1990; Jones and Nishiguchi, 2004; Kau et al, 2011; Hooper et al, 2012; Fraune et al, 2015; Gromek et al, 2016). Interactions between hosts’ immune systems and the resident microbiota are often essential in the establishment and maintenance of beneficial associations (Stappenbeck et al, 2002; Nyholm and Graf, 2012; Buchon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%